Detailed β-(1→3)-D-glucan and mannan antigen kinetics in patients with candidemia - Träger, Johannes; Dräger, Sarah; Mihai, Sidonia; Cipa, Franziska; Grawitz, Andrea Busse; Epting, Thomas; Meyer, Renate; Rappold, Elfriede; Held, Jürgen (Journal of Clinical Microbiology, 2023)
Fungal antigens such as β-(1→3)-D-glucan (BDG) or mannan (Mn) are useful for detection of candidemia. However, detailed data on serum levels before diagnosis and during treatment are scarce. We conducted a prospective study at two German tertiary care centers for 36 months. Sera from adult patients with candidemia were tested for BDG (Fungitell assay) and Mn (Platelia Candida Ag-Plus assay). For each patient, the clinical course and biomarker kinetics were closely followed and compared. 1,243 sera from 131 candidemia episodes and 15 relapses were tested. In 35% of episodes, empirical therapy included an antifungal drug. Before blood culture sampling, BDG and Mn levels were elevated in 62.4% and 30.8% of patients, respectively. Sensitivity at blood culture sampling was 78.6% (BDG) and 35.1% (Mn). BDG levels of non-survivors were significantly higher than those of survivors. During follow-up, a therapeutic response was associated with decreasing BDG and Mn levels in 84.3% or 70.5% of episodes, respectively. A median increase of 513 pg BDG/mL and 390 pg Mn/mL indicated a relapse of candidemia with a sensitivity of 80% or 46.7%, respectively. In 72.9% and 46.8% of patients, increasing BDG or Mn levels were associated with a fatal outcome. Prior to discharge, BDG and Mn levels had dropped or normalized in 65.7% or 82.1% of patients, respectively. Summarising, in patients with candidemia, biomarker positivity usually precedes culture positivity. Relapses are mostly accompanied by secondary biomarker increases. Rising concentrations of BDG and Mn predict lethality, whereas decreasing levels suggest a favorable outcome in the majority of patients.
CRIS-Team Scopus Importer:2023-12-08
Keywords: biomarker; Candida; Fungitell; glucan; mannan; Platelia; sepsis